Tingkat Partisipasi Anggota Kelompok Wanita Tani dalam Program P2L di Kecamatan Karangpandan Kabupaten Karanganyar - Pinastri, Lintang Mukti; Anantanyu, Sapja; Widiyanto, Widiyanto (Jurnal KIRANA, 2024)
P2L or Pekarangan Pangan Lestari is a government program in an effort to realize household food security through a movement to utilize yard land. The participation of farmer women group members is a determining factor for the sustainability of this program. This study aims to: (1) Assess the level of participation of Farmer Women Group members in the P2L program, (2) Analyzing the relationship between factors influencing the participation of members of the Farmer Women's Group in the P2L program in Karangpandan District, Karanganyar Regency. The basic method used in this research is quantitative with a research instrument using a questionnaire. Sampling was done using proportional random sampling technique as many as 66 respondents. Data analysis using the spearman rank test. The results showed: (1) the level of participation of farm women group members as a whole is in the high category, (2) factors that are significantly related to the participation of KWT members, namely formal education, non-formal education, income, number of family members, and the level of support from husband/family.